Penguatan Literasi Digital Keluarga dalam Menghadapi Link Scam dan Risiko Penyalahgunaan AI di RW 03 Kalipancur - Indra Abdam Muwakhid; Dewi Nurdiyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Digital transformation has reshaped community life by increasing internet dependency in daily communication, financial transactions, and public services. However, this rapid development has also intensified cybersecurity risks, particularly link-based scams and the misuse of Artificial Intelligence (AI). Limited digital literacy at the family level makes communities vulnerable to phishing attacks, personal data breaches, and AI-generated fraud. This community service program aimed to strengthen digital literacy among residents of RW 03 Kalipancur, Semarang, through participatory education focusing on link scam detection and responsible AI usage. The program involved interactive lectures, case discussions, simulations, and pre-test and post-test evaluations with 18 participants from family groups, PKK cadres, and elderly residents. The results showed a significant increase in understanding, from an average pre-test score of 43% to a post-test score of 84%. Beyond knowledge improvement, participants demonstrated increased awareness and behavioral change toward safer digital practices. The findings suggest that community-based participatory approaches effectively enhance family-level digital resilience and can serve as a replicable empowerment model in other communities facing similar digital threats.